2014
DOI: 10.3855/jidc.3726
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two rapid influenza tests in comparison to reverse transcription-PCR for influenza A diagnosis

Abstract: Introduction: The influenza A virus is responsible for high morbidity and mortality in children and adults worldwide. Thus, a rapid, sensitive, and specific diagnosis tool is required. Methodology: An immunofluorescence assay (DFA) and a lateral-flow immunochromatographic assay were compared with RT-PCR for detection of the influenza A virus in 113 nasopharyngeal wash samples obtained from pediatric patients. Samples were collected between July and December 2009, during the pandemic outbreak of influenza A H1N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, such tests still require extensive hands-on time and have an average analytical turnaround time of 3-4 hours. Rapid immunochromatographic tests for the detection of viral antigens have an average turnaround time of 20 min, excellent specificity (Sp), but still are hampered by limited sensitivity (Se) that necessitate to confirm negative results using a technique presenting optimal Se (Aslanzadeh et al, 2008;Falsey et al, 2005;Paulson, 2009;Zazueta-Garcia et al, 2014). The GeneXpert system (Cepheid, France) is designed for nucleic acid extraction, RT-PCR amplification, and real-time detection using a single-use disposable cartridge and an automated platform.…”
Section: Introductionmentioning
confidence: 99%
“…However, such tests still require extensive hands-on time and have an average analytical turnaround time of 3-4 hours. Rapid immunochromatographic tests for the detection of viral antigens have an average turnaround time of 20 min, excellent specificity (Sp), but still are hampered by limited sensitivity (Se) that necessitate to confirm negative results using a technique presenting optimal Se (Aslanzadeh et al, 2008;Falsey et al, 2005;Paulson, 2009;Zazueta-Garcia et al, 2014). The GeneXpert system (Cepheid, France) is designed for nucleic acid extraction, RT-PCR amplification, and real-time detection using a single-use disposable cartridge and an automated platform.…”
Section: Introductionmentioning
confidence: 99%
“…Though studies have shown that PCR is more sensitive than other test methods, ( 31 , 32 ) our pooled results from other testing methods (not including APAAP and immunoassay) had higher positivity than PCR. This may be because the use of PCR was largely limited to the resourceful southern provinces that have lower proportions of influenza-associated hospitalizations compared with the northern provinces.…”
Section: Discussionmentioning
confidence: 80%
“…This shows that the colloidal gold method alone is insufficient to discriminate between influenza and influenza-like disease. Studies have shown that the PPV range for a rapid influenza test kit is 30-80% 11,12 . Moreover, Eggers et al 13 reported that the sensitivity and NPV of a rapid influenza test were 40-50% and 55-56%, respectively.…”
Section: Discussionmentioning
confidence: 99%